THE SINO-INDIAN RELATIONS FOR INFLUENCE IN SOUTH ASIA: THE CASE OF BELT AND ROAD INITIATIVE (BRI) - Ibañez, Pablo (2023)
This article intends to analyze, from the principles of neoclassical realism and geoeconomics, the perspectives about the Chinese initiative for investments in infrastructure, the Belt and Road Initiative (BRI). Will be exposed discussions on Chinese economic and military development, the implementation of the BRI in South Asia and the issues resulting from disputes over the regional leadership role. The China-Pakistan-India triad is central to the analysis by highlighting possibilities for cooperation as well as the resurgence of geopolitical rivalries. The China-Pakistan Economic Corridor (CPEC) summarizes the obstacles between countries as they pass through historically conflicted zones, such as Kashmir, but allows to follow the increasing leadership posture assumed by Beijing. At the other extreme, the Sino-Indian relationship unfolds in discontents that are part of a regional and global narrative of uncertainty about the Chinese capabilities.